Thermodynamic properties of potential alternative refrigerant HFO-1234ze(Z) - Phan, Thi Thu Huong; Lai, Ngoc Anh; Nguyen, Nguyen An; Ta, Van Chuong (JST: Engineering And Technology For Sustainable Development, 2022)
Cis-1,3,3,3-Tetrafluoropropene HFO-1234ze(Z) is an environmentally friendly potential alternative refrigerant for heat-pump application. The accurate thermodynamic properties of HFO-1234ze(Z) in both single-phase and two-phase regions are of vital importance in the study, evaluation, investigation of refrigeration system, heat pump and other equipment using the HFO-1234ze(Z) as working fluid. So, this paper aims to provide an accurate lgP-h diagram and the thermodynamic properties in both single-phase and two-phase regions. The accuracy of this published data and the lgP-h diagram was evaluated by comparing this data with available experimental data. The study shows that the average absolute deviations between our values and experimental data for vapourur pressure, saturated liquid density, subcooled liquid density and gaseous pressure are 0,34%, 0,42%, 0,60%, and 0,99%, respectively. Additional evaluations for the ideal gas heat capacities and speed of sound are available in this work. The average absolute deviations between calculated values and published data for compressed liquid speed of sound, gaseous speed of sound data and ideal gas heat capacity are 2.2%, 0,98%, 0,57%, respectively.